Recent Advances in Identification and Characterization of β-Adrenoceptor Agonists and Antagonists - Hieble, J. Paul (Current Topics in Medicinal Chemistry, 2007)
The three β-adrenoceptor subtypes (β1, β2, β3) represent important therapeutic targets. The use of β2- adrenoceptor agonists as bronchodilators and β1 or β1/β2 antagonists as antihypertensives is well established; research is ongoing in these areas to refine pharmacodynamic properties. It is also feasible to design molecules combining β-adrenoceptor affinity with other pharmacophores. This is facilitated by the ability to confer β- adrenoceptor antagonist activity via attachment of a phenylethanolamine moiety or to incorporate diverse structural elements in the N-alkyl substituent of a β-adrenoceptor agonist or antagonist. β3-Adrenoceptor agonists have not yet been successfully developed as drugs for any therapeutic indication; nevertheless, during the past few years many highly potent and selective β3-agonists have been reported, some with good oral bioavailability. Selective β3-adrenoceptor antagonists have also been identified; useful pharmacological tools are now available for the evaluation of the functional role of each β-adrenoceptor subtype.
Keywords: phosphodiesterase